Production of camu camu plants with different organic substrates in conventional nursery bed (Scientia Agropecuaria, 2013)
The aim was to verify the initial development of camu camu plants with different organic substrates in conventional nursery bedding microsprinkler irrigation and shade management Chromatine® mesh with 50% red light. We used genetic material from mother plants Germplasm Bank of INIA-camu camu Iquitos, seeds were germinated in decomposed sawdust and kept for a period of 40 days after subculturing was performed with 10 cm in height in different substrates according treatments in nursery beds with dimensions of 1.20 m wide x 10 m long with a depth of 30 cm. After conducting assessments of height (cm) and basal diameter (mm) for a period of 120 days, it was found that the substrate manure has become the substrate for greater efficiency in plant development camu camu substrate followed by humus worm.
Keywords: Myrciaria dubia; nursery; substrate; chicken manure; worm compost